Nauczyciel mądrości i wychowawca – mądrościowy wzorzec ojca - Popielewski, Wojciech (Verbum Vitae, 2015)
Biblical wisdom literature of Israel draws attention first of all because it deals with the life of person involved in the nearest environment. The books of wisdom don’t speak of big historical traditions of God’s people but they try to form a man to help him to adapt himself to the order established by God. The family, with a figure of father, is the first step of maturing on the way of wisdom. The father has a double responsibility: he is a master of wisdom and a tutor for his own son. He transfers a treasure of his experience to his son. He leads him, sometimes with severity, to the future of happiness. The poem of the book of Sirach (30, 1-13) is a good example of that. We see here the wisdom of father who is at the end of his own life and who has the unique desire: to see the son as his follower. Even if he is requiring, he does it for the good of his child. Making so he ends his life as a responsible master of wisdom.